We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+2
33
1
avatar+6 

If (8z − 9)(8z + 9) = az2 − b, what is the value of a?

 Mar 14, 2019
 #1
avatar+775 
+14

(8z − 9)(8z + 9) = az2 − b

 

First you must swich sides:

az * 2 - b = (8z - 9) (8z + 9)

 

Add b to both sides

az * 2 - b = (8z - 9) (8z + 9)

az * 2 - b + b = (8z - 9) (8z + 9) + b

Then symplify

az * 2 = (8z - 9) (8z + 9) + b

 

Then divide both sides by z * 2

\(\frac{az*2}{z * 2}\) \( = \frac{(8z - 9)(8z + 9)}{z*2}+\frac{b}{z*2}\)

Then symplify

\(a = \frac{(8z-9)(8z+9)+b}{2z}\)

 

Hope this helps ;P

 Mar 14, 2019

22 Online Users

avatar
avatar
avatar
avatar